1996
DOI: 10.1002/(sici)1097-4644(19960915)62:4<443::aid-jcb2>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4 inhibits hepatocyte growth factor-induced invasion and migration of colon carcinomas

Abstract: Hepatocyte growth factor (HGF) is known to have a number of biological properties including promoting tumor progression of human carcinomas. Metastasis involves a number of events that are attributed to induction by paracrine factors such as HGF. Identification of natural inhibitors of these events would allow better control of tumor progression. Recently we demonstrated that interleukin 4 (IL-4) can regulate proliferation of various human carcinoma cell lines. In the present study, we used established human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Activation of PKC can lead to the phosphorylation of c-Met on serine 985, and in turn, inhibition of the receptor's intrinsic tyrosine kinase activity (Gandino et al, 1994). IL-4 blocked the HGF-stimulated migration of colon carcinoma cells in a cell-matrix invasion assay (Uchiyama et al, 1996). In that study, IL-4 also inhibited HGF-stimulated expression of matrix metalloproteinases (MMP)-1, -2, and -9.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Activation of PKC can lead to the phosphorylation of c-Met on serine 985, and in turn, inhibition of the receptor's intrinsic tyrosine kinase activity (Gandino et al, 1994). IL-4 blocked the HGF-stimulated migration of colon carcinoma cells in a cell-matrix invasion assay (Uchiyama et al, 1996). In that study, IL-4 also inhibited HGF-stimulated expression of matrix metalloproteinases (MMP)-1, -2, and -9.…”
Section: Discussionmentioning
confidence: 79%
“…The biological eects of IL-4 are also inÂŻuenced by other cytokines and growth factors. IL-4 complements IL-2 in T-cell tumor lines for ex vivo autocrine growth and for in vivo tumorigenicity (Hassuneh et al, 1997), acts synergistically with platelet-derived growth factor (PDGF) in mitogenesis (Patel et al, 1996), and inhibits HGFstimulated migration of colon carcinoma cells (Uchiyama et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…26) IL-12 and g-linolenic acid inhibit HGF-induced tumor migration via up-regulation of cell-surface Ecadherin. 27,28) IL-4 is also shown to inhibit HGF-induced tumor migration but its mechanism is unknown. 29) In contrast, evodiamine suppressed HGF-induced tumor migration by acting to repress the cell spreading.…”
Section: -4)mentioning
confidence: 99%
“…The association of these findings with tumors manifesting known pathologic features consistent with increased prohferation suggests a possible etiology for their presence. Recently it has been shown that free tumor-associated DNA can be identified in the serum and plasma from patients with melanoma, breast, lung, renal, gastrointestinal and head and neck tumors (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Furthermore a high-quality concordance has been shown to exist between the genetic alterations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The c-Met oncogene encodes for hepatocyte growth factor receptor, which is a tyrosine kinase ti-ansmembrane protein receptor (24). Hepatocyte growth factor binding to the receptor transduces a signal for cell dissociation, motihty, and mitogenesis (25,26). Its expression in breast cancer has been shown recently to independently predict survival (27).…”
mentioning
confidence: 99%